Down the Final Stretch: State Societal Settlements’ Res Judicata Repercussions - Ángel R. Oquendo (Washington University Global Studies Law Review, 2019)
Like the chorus in Shakespeare’s Henry the Fifth, those who proceed on behalf of society at large should have both the first and last word. They should possess the capacity to undertake this act of representation, whether in or out of court, with forcefulness and finality. Indeed, a genuine representative should not have to run the risk of others thereafter embarking upon the matter anew and standing in for whomever she is representing, as well as casting aside her effort as irrelevant, insufficient, or illegitimate. Therefore, a societal settlement, particularly when negotiated by the authorities, may have not only contractual but also procedural (or preclusive) implications, which (partly independently of intent) shield the contractors from litigation as well as liability. To that end, it may or may not, depending on the jurisdiction, require the judiciary’s endorsement in order to constitute the functional equivalent of a judgment. U.S. and civil-law principles of preclusion bar a subsequent suit insofar as it involves the same real party in interest (namely, the whole citizenry) and assertion (or cause and object) as its amicably averted antecedent counterpart. Judges and lawmakers in the United States, as well as Latin America, have invariably conceded these actions an erga omnes effect; in other words, against anyone with standing who might try to reignite the controversy. Settlers in these cases normally neither compromise on the underlying entitlements nor contract on the rights of someone else. In fact, they may and should vindicate these entitlements fully and facilitate the collective conciliation of claims based on collectivity’s own rights. The government, for its part, enjoys plenty of legitimacy to play this role and to settle on, as well as prosecute, these entitlements. In these disputes, the settling or suing actor steps into the shoes of the broader community. The latter, as the interested claimant, may not subsequently take another bite at the apple through a different spokesperson. Otherwise, it would unfairly and inefficiently burden, respectively, its opponents and the adjudicating tribunals in its quest for a windfall. Consequently, the trans-individual settlements and suits at stake should strengthen, rather than weaken, from a punctilious adherence to the requirements of res judicata. They should thereby further legitimate themselves and perhaps even solidify the political and social support from which they benefit.
Keywords: preclusion; settlement; Latin America; settle; entitlements